Color stability of modern composites subjected to different periods of accelerated artificial aging - Drubi-Filho,Brahim (2012)
The aim of this study was to evaluate the color stability of composites subjected to different periods of accelerated artificial aging (AAA). A polytetrafluorethylene matrix (10 x 2 mm) was used to fabricate 24 test specimens of three different composites (n=8): Tetric Ceram (Ivoclar/Vivadent); Filtek P90 and Z250 (3M ESPE), shade A3. After light activation for 20 s (FlashLite 1401), polishing and initial color readout (Spectrophotometer PCB 687; BYK Gardner), the test specimens were subjected to AAA (C-UV; Comexim), in 8-h cycles: 4 h exposure to UV-B rays at 50°C and 4 h condensation at 50°C. At the end of each cycle, color readouts were taken and the test ended when the mean value of ΔE attained a level ≥3.30. Tetric Ceram presented alteration in ΔE equal to 3.33 in the first aging cycle. For Filtek P90 and Z250, two (ΔE=3.60) and four (ΔE=3.42) AAA cycles were necessary. After each cycle, there was a reduction of luminosity in all the samples (ΔL). It was concluded that a short period of AAA was sufficient to promote clinically unacceptable color alteration in composites, and that this alteration was material-dependent.